Liquid dosage forms : laboratory practices - Tichý, Eduard; Špaglová, Miroslava; Bartoníková, Kamila (Comenius University in Bratislava, 2024)
The textbook is a practical guide designed for students and professionals in pharmaceutical sciences. This textbook provides a detailed overview of the formulation, preparation, and evaluation of liquid dosage forms, including solutions, suspensions, and emulsions. With step-by-step laboratory practices, it bridges theoretical knowledge with hands-on experience, emphasizing key concepts such as stability, compatibility, and quality control. The book serves as an invaluable resource for understanding the essential principles and techniques needed for the development and analysis of liquid pharmaceutical formulations.----------Učebnica je praktická príručka určená pre študentov a odborníkov vo farmaceutických vedách. Táto učebnica poskytuje podrobný prehľad o formulácii, príprave a hodnotení kvapalných liekových foriem vrátane roztokov, suspenzií a emulzií. S laboratórnymi postupmi krok za krokom spája teoretické znalosti s praktickými skúsenosťami, pričom kladie dôraz na kľúčové pojmy, ako je stabilita, kompatibilita a kontrola kvality. Kniha slúži ako neoceniteľný zdroj na pochopenie základných princípov a techník potrebných na vývoj a analýzu tekutých farmaceutických prípravkov.